Isolation of secondary metabolites from quercus infectoria galls and their antimicrobial activity - Sulaiman, Fatimatul Akma; Darnis, Deny Susanti; Mohamed Iqbal, Mohammad Anwar; Miskam, Mazidatulakmam Akmam (2015)
The evolution of resistant microorganism towards available antibiotics has gain interest among scientists to search for more effective antimicrobial compounds. Plant is believe to have antimicrobial properties as the extract is used in food industry, pharmaceuticals and alternative medicine. The aims of this study are to isolate secondary metabolites from Q. infectoria galls and to elucidate structure of the isolated compound using spectroscopic techniques and determination of antimicrobial activity. The galls were extracted with organic solvent using soxhlet apparatus and fractionated using chromatographic techniques. The isolated compounds were characterized using spectroscopic techniques such as UV spectrophotometer, Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance (NMR) and Mass Spectrometry (MS). The antimicrobial activities are determined using disc diffusion method, determination of MIC, MBC, MFC and synergistic effect. The disc diffusion test against Staphylococcus aureus showed zone of inhibition 7 mm (n-hexane extract) and 9 mm (methanol extract). Meanwhile, dichloromethane extract showed no inhibition against S. aureus. It is expected that the isolated compound have antimicrobial properties and synergistic effect in combination with standard antibiotic.